Partial Gene Deletions of PMP22 Causing Hereditary Neuropathy with Liability to Pressure Palsies - Cho, Sun-Mi (Case Rep Genet, 2014)
Hereditary neuropathy with liability to pressure palsies (HNPP) is an autosomal neuropathy that is commonly caused by a reciprocal 1.5 Mb deletion on chromosome 17p11.2, at the site of the peripheral myelin protein 22 (PMP22) gene. Other patients with similar phenotypes have been shown to harbor point mutations or small deletions, although there is some clinical variation across these patients. In this report, we describe a case of HNPP with copy number changes in exon or promoter regions of PMP22. Multiplex ligation-dependent probe analysis revealed an exon 1b deletion in the patient, who had been diagnosed with HNPP in the first decade of life using molecular analysis.